2020
DOI: 10.1055/s-0040-1708475
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Thoracic Surgery in Early Stage of Pediatric Pleural Empyema Improves Outcome

Abstract: Objectives The aim of this study was to observe outcomes of early decortication in a treatment of pleural empyema using video-assisted thoracoscopic surgery (VATS). Methods The case records of 21 pediatric patients who underwent VATS for empyema between 2009 and 2019 were retrospectively reviewed. Patients were observed based on demographic, laboratory, and clinical data, as well as treatment outcomes. Results Out of a total of 59 patients treated for pleural empyema, 21 (10 male and 11 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
(68 reference statements)
2
7
0
1
Order By: Relevance
“…On the one hand, the appropriate stage of empyema for surgical treatment required further investigation 19 . For example, Pogorelić et al found that in the early stage of pleural empyema, video-assisted thoracic surgery could improve the outcome of pediatric patient 20 . In contrast, some authors recommended intrapleural fibrinolytic treatment in patients with stage 1 and 2 empyema 21 .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the appropriate stage of empyema for surgical treatment required further investigation 19 . For example, Pogorelić et al found that in the early stage of pleural empyema, video-assisted thoracic surgery could improve the outcome of pediatric patient 20 . In contrast, some authors recommended intrapleural fibrinolytic treatment in patients with stage 1 and 2 empyema 21 .…”
Section: Discussionmentioning
confidence: 99%
“…), 10 момчета и 11 момичета, с емпием на плеврата през периода между 2009 г. и 2019 г. в гр. Сплит, Хърватска (12). В първи стадий на заболяването са две деца, във втори -четири деца, а в трети -15 деца.…”
Section: резултатиunclassified
“…PAL can complicate spontaneous pneumothorax, empyema, pulmonary infection, barotrauma, chest trauma, lung surgery, and other underlying lung diseases. 2,5,6 Specifically in children, necrotizing pneumonia and empyema are common causes, and their incidences have increased over recent decades . 7,8 Data from studies of adults show that some air leaks are prolonged, although many resolve spontaneously with conservative management.…”
Section: Introductionmentioning
confidence: 99%
“…PAL may be caused by alveolar‐pleural fistula or bronchopleural fistula (BPF); these are not always distinguishable in the clinical setting. PAL can complicate spontaneous pneumothorax, empyema, pulmonary infection, barotrauma, chest trauma, lung surgery, and other underlying lung diseases 2,5,6 . Specifically in children, necrotizing pneumonia and empyema are common causes, and their incidences have increased over recent decades 7,8 .…”
Section: Introductionmentioning
confidence: 99%